Application of Determiners in Phraseological Units Containing Names of Human Body Parts - Marta Lackova (Communications - Scientific letters of the University of Zilina, 2010)
The article deals with formal expressive means of the category of determination which are applied in phraseological units of the English language containing names of human body parts (nouns ear, eye, face, foot, hand, head, heart are the focus of our attention). At first, the article provides a brief introduction into the linguistic area of determination. Three types of determiners (predeterminers, central determiners, postdeterminers) are classified in order to provide background information for further research. Moreover, general rules dealing with the use of articles with reference to body parts are introduced. The above mentioned types of determiners find their realization also within the framework of the analysed phraseological units. Possessive pronouns, the definite, indefinite and zero articles represent the most spread types of determiners in the studied area.